Leishmania donovani Secretory Mevalonate Kinase Regulates Host Immune Response and Facilitates Phagocytosis - Tanvir Bamra; Taj Shafi; Sushmita Das; Manjay Kumar; Manas Ranjan Dikhit; Ajay Kumar; Ashish Kumar; Kumar Abhishek; Krishna Pandey; Abhik Sen; Pradeep Das (Frontiers in Cellular and Infection Microbiology, 2021)
Summary StatementLeishmania secretes over 151 proteins during in vitro cultivation. Cellular functions of one such novel protein: mevalonate kinase is discussed here; signifying its importance in Leishmania infection.Visceral Leishmaniasis is a persistent infection, caused by Leishmania donovani in Indian subcontinent. This persistence is partly due to phagocytosis and evasion of host immune response. The underlying mechanism involves secretory proteins of Leishmania parasite; however, related studies are meagre. We have identified a novel secretory Leishmania donovani glycoprotein, Mevalonate kinase (MVK), and shown its importance in parasite internalization and immuno-modulation. In our studies, MVK was found to be secreted maximum after 1 h temperature stress at 37°C. Its secretion was increased by 6.5-fold in phagolysosome-like condition (pH ~5.5, 37°C) than at pH ~7.4 and 25°C. Treatment with MVK modulated host immune system by inducing interleukin-10 and interleukin-4 secretion, suppressing host’s ability to kill the parasite. Peripheral blood mononuclear cell (PBMC)-derived macrophages infected with mevalonate kinase-overexpressing parasites showed an increase in intracellular parasite burden in comparison to infection with vector control parasites. Mechanism behind the increase in phagocytosis and immunosuppression was found to be phosphorylation of mitogen-activated protein (MAP) kinase pathway protein, Extracellular signal-regulated kinases-1/2, and actin scaffold protein, cortactin. Thus, we conclude that Leishmania donovani Mevalonate kinase aids in parasite engulfment and subvert the immune system by interfering with signal transduction pathways in host cells, which causes suppression of the protective response and facilitates their persistence in the host. Our work elucidates the involvement of Leishmania in the process of phagocytosis which is thought to be dependent largely on macrophages and contributes towards better understanding of host pathogen interactions.